1984
DOI: 10.1111/j.1745-4530.1984.tb00303.x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Heat and Mass Transfer During the Oven Roasting of Meat

Abstract: The roasting (baking) of meat involves both heat and mass transfer. A mathematical model which describes the roasting process as it occurs in a conventional oven is presented. Numerical solutions are presented for several different roasting conditions and the results are compared to available experimental results. A significant fraction of the energy required for roasting is associated with the evaporation of water and this needs to be considered in modeling the roasting process. Water losses due to mass trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 9 publications
1
10
0
1
Order By: Relevance
“…They found that varying partial pressure of water vapor during the roasting process affected rate of moisture loss by evaporation. Similar results were also reported by Godsalve et al (1977a, b), Hung et al (1978) and Singh et al (1983). de Baerdemaeker et al (1977) showed how heat transfer problems may be solved using the finite element method in roasting beef and chicken.…”
Section: Introductionsupporting
confidence: 85%
“…They found that varying partial pressure of water vapor during the roasting process affected rate of moisture loss by evaporation. Similar results were also reported by Godsalve et al (1977a, b), Hung et al (1978) and Singh et al (1983). de Baerdemaeker et al (1977) showed how heat transfer problems may be solved using the finite element method in roasting beef and chicken.…”
Section: Introductionsupporting
confidence: 85%
“…2b, where only a thin darker (mainly due to browning reactions) layer is visualized, mostly in the upper regions. Other researchers found similar behaviour during meat cooking in domestic ovens (Bengtsson et al, 1976;Singh et al, 1984;Obuz et al, 2002). Finally, Table 1 summarizes the cooking times for all tested conditions.…”
Section: Aardmentioning
confidence: 73%
“…In this sense, several authors have studied different meat products, i.e. beef (Goñi et al, 2008b;Obuz et al, 2002Obuz et al, , 2004Singh et al, 1984;Townsend et al, 1989a,b), whole unstuffed turkeys (Chang et al, 1998). Goñi et al (2008b) and Obuz et al (2002) found that the average error between predicted and experimental weight losses is 20-22%.…”
Section: Introductionmentioning
confidence: 96%
“…With this in mind, a greater understanding of cooking processes is required in order to help food processors identify and implement optimal processing conditions. Mathematical models of certain meat-cooking processes may be found in the literature, including models for immersion cooking (Burfoot & Self, 1988), contact frying (Dagerskog, 1979;Houšová & Topinka, 1985;Ikediala, Correia, Fenton, & Ben-Abdallah, 1996;Pan, Singh, & Rumsey, 2000), convection oven roasting (Chang, Carpenter, & Toledo, 1998;Chen, Marks, & Murphy, 1999;Obuz, Powell, & Dikeman, 2002;Singh, Akins, & Erickson, 1984), and microwave oven roasting (Verboven, Datta, Anh, Scheerlink, & Nicolaï, 2003). The heat transfer coefficient (h) between the surface of the product and its surroundings is an essential parameter of most heat transfer models.…”
Section: Introductionmentioning
confidence: 99%